La llamada existencia de Dios en Santo Tomás: un replanteo del problema. (2010)
The central thesis of this article is that the debate about the ways of Aquinas is held not only for obvious cultural reasons; but an internal problem to Thomism today. This first reviewed the traditional objections (Kant; positivism; Heidegger); we review and evaluate the traditional responses from various thomists (Fabro; Gilson; Llano; Welte; Ferro) and then suggest our proposal; from a re-development of relationship between reason and faith; awareness of the hermeneutic circle and a step forward in the notion of Christian philosophy.